2022
DOI: 10.3390/pr10030498
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Effects and Mechanisms of Alkaline Natural Mineral Water and Distilled Water on Ethanol-Induced Gastric Ulcers In Vivo and In Vitro

Abstract: Studies have proven that alkaline water has a protective effect on gastric diseases. However, the underlying mechanism is not clear. Moreover, in some countries, especially in China, purified water (distilled water) is also an important form of drinking water, while its protective effect on gastric diseases is still unknown. This study aimed to compare the effects of distilled water (pH = 5.6 ± 0.3) and alkaline natural mineral water (pH = 9.3 ± 0.6) on ethanol-induced gastric ulcers in mice and to further cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Alkaline water is a liquid or water that has a pH an acidic condition in our body and maintain our body in an alkaline environment [22]. The fluoride content is useful for rebuilding previously weakened tooth enamel, slowing the loss of minerals from tooth enamel, stopping the initial process of cavity, and preventing the growth of oral bacteria that damage teeth [23]. The chromium element within the permissible limits functions to help convert glucose in the blood into body energy, so that glucose in the blood can decrease.…”
Section: B Chemical Parametersmentioning
confidence: 99%
“…Alkaline water is a liquid or water that has a pH an acidic condition in our body and maintain our body in an alkaline environment [22]. The fluoride content is useful for rebuilding previously weakened tooth enamel, slowing the loss of minerals from tooth enamel, stopping the initial process of cavity, and preventing the growth of oral bacteria that damage teeth [23]. The chromium element within the permissible limits functions to help convert glucose in the blood into body energy, so that glucose in the blood can decrease.…”
Section: B Chemical Parametersmentioning
confidence: 99%
“…Verma et al [5] deliberately studied the water quality index of ground water in Ganeshwar and Chala villages of Neemkathan block in Sikar India and considered the alkalinity as a WQI parameter in the water and observed the value of alkalinity between 250 to 450 mg/L CaC03. Sun et al [6] investigated the effect and mechanism of alkaline water (pH = 9.3 ±0.6) and distilled water (pH = 5.6 ± 0.3) on ethanol-induced gastric ulcers in Vivo and in vitro and found that the pepsin activity was significantly declined after alkaline water treatment as compared with distilled water. Wilson [7] developed the water quality notes regarding the alkalinity and hardness in the University of Florida and said that the "Alkalinity is a measure of the acid neutralizing capacity of water".…”
Section: Open Accessmentioning
confidence: 99%
“…A significance of p>0.05 in the pH, total chromium and MPN Coliform showed differences in concentrations in the parameters. The difference in the concentration of mineral content is influenced by the surrounding environmental conditions [13]. Based on the results of laboratory examinations, the alkaline water production process in this study has been carried out using the proper method so that the microbiological quality of the alkaline water traded in the market is maintained.…”
Section: Parameter Chrommentioning
confidence: 99%
“…If the environment in our bodies has changed from oxygen in an acidic environment to an alkaline environment full of oxygen, viruses, bacteria and fungi cannot live. Ionized Alkaline Water can prevent acidic conditions in our body and make our body an alkaline environment [22] [13].…”
Section: Organic Materials Decomposition Processmentioning
confidence: 99%